The Potential Significance of ABO Genotyping for Donor Selection in Kidney Transplantation - Zhou, Yi; Wang, Yuchen; Ni, Haiqiang; Deng, Wenfeng; Liu, Ding; Xu, Jian; Cui, Naiqian; Wu, Yihan; Fu, Shaojie; Xiao, Lulu; Liu, Hailiang; Qi, Ka; et al. (Frontiers in Immunology, 2020)
Background: The ABO blood group system is clinically important in kidney transplantation, but ABO genotyping fails to attract sufficient attention in some countries and regions. We identified one case of early graft dysfunction due to an ABO genotype mismatch. Here, we performed ABO genotyping in blood samples, analyzed grouping discrepancies, and investigated the weak A subgroup frequency in kidney transplantation candidates. Methods: Blood samples from 302 uremic patients with grouping discrepancies and 356 uremic patients with type A blood were analyzed using standard serologic serotyping techniques. The ABO genotypes and alleles were analyzed by polymerase chain reaction sequence-specific primer (PCR-SSP) and sequence-based typing (PCR-SBT). Results: All 302 uremic patients with grouping discrepancies carried weak ABO subgroup alleles and 77.48% carried irregular ABO antibodies. The discrepancy rate between serotyping and genotyping was 42.38%, and the mismatching rate of donor selection according to serotype reached 88.74%. And 2.53% of 356 uremic patients with type A blood were determined to be in the weak A subgroup, which was a higher percentage than that observed in the healthy Chinese population (0.53%) by serological screening, but much lower than that observed in Caucasians (20%). Conclusion: We revealed the high risk of blood type misjudgment and genetically ABO-mismatched transplantation if serological test was performed only in blood-group typing. Improved precision of ABO genotyping is crucial for successful kidney transplantation and reasonable organ allocation.